2020
DOI: 10.3390/su12104250
|View full text |Cite
|
Sign up to set email alerts
|

Trip and Personal Characteristics towards the Intention to Cycle in Larnaca, Cyprus: An EFA-SEM Approach

Abstract: Mobility is one of the most important and challenging aspects that influence climate change, air quality, and especially the quality of citizens’ lives. Therefore, creating sustainable transport solutions makes way for different modes of transport such as the bicycle, which is continuously gaining more supporters, due to the health, economic, and environmental benefits that it provides. However, cyclists are facing several barriers (e.g., lack of infrastructure), a fact that keeps away commuters from using a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Each item presents a 'loading factor' (which should be >0.3 or >0.4 depending on the literature), representing the 'correlation strength' with the factor (Brown 2015, Watkins 2018. Additionally, overall indicators of adequacy such as KMO > 0.5 suggest that the factor analysis is suitable for all the items included (Nikolaou et al 2020). Variables below the cut-off value should be removed from the analysis, and the number of factors should be adjusted accordingly before starting a new iteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each item presents a 'loading factor' (which should be >0.3 or >0.4 depending on the literature), representing the 'correlation strength' with the factor (Brown 2015, Watkins 2018. Additionally, overall indicators of adequacy such as KMO > 0.5 suggest that the factor analysis is suitable for all the items included (Nikolaou et al 2020). Variables below the cut-off value should be removed from the analysis, and the number of factors should be adjusted accordingly before starting a new iteration.…”
Section: Discussionmentioning
confidence: 99%
“…The EFA seeks to identify latent structures by 'grouping' similar items through iterative statistical processes, which would become the groups that are subsequently included in the SEM. During this process those items considered to not be sufficiently related to the various latent constructs, are discarded in order to have a 'cleaner' dataset for the SEM analysis (Nikolaou et al 2020).…”
Section: Research Approachmentioning
confidence: 99%
“…The EFA results of the rst phase of the investigation showed that the Kaiser-Meyer-Olkin (KMO) value was 0.975, higher than 0.6, and the result of Bartlett's test was signi cant (χ2 = 46123.739, p < 0.001), both of which indicated a strong correlation among the items; the data were applicable for EFA [44,45].…”
Section: Exploratory Factor Analysis and Research Hypothesesmentioning
confidence: 91%
“…The EFA results showed that the Kaiser-Meyer-Olkin (KMO) value was 0.966, which was higher than 0.6, indicating the appropriateness of conducting EFA [49]. Further, the result of Bartlett's test was signi cant ( =33912.366, P<0.001), indicating that the relationship among the items was strong and that the data were suitable for EFA [50].…”
Section: Exploratory Factor Analysis and Research Hypotheses Exploratmentioning
confidence: 95%